Relationship between Fractal Dimension of Fragmentation Degree and Energy Dissipation of Rock-Like Materials under Initial Stress - Ying Xu; Jinjin Ge; Hailong Li; Rongzhou Yang; Kun Wang; Shi Hu (Shock and Vibration)
In order to obtain the relationship between fractal dimension and energy dissipation of rock-like materials under initial stress state, a variable cross-section split Hopkinson pressure bar (SHPB) test system with active confining pressure loading device was used to carry out impact compression and splitting tests on cemented sand specimens. The impact test results show that (1) the prediction value on the fragmentation degree of cemented sand specimens by using the fractal model is basically consistent with the screening results of actual test, which verifies the applicability of the fractal calculation model given in this study; (2) the more the fracture energy dissipated in the crushing process of cemented sand specimens, the more serious the fragmentation degree is, and accordingly the larger the fractal dimension is, that is, the fracture energy is positively correlated with the fractal dimension; (3) there is an exponential relationship between the fractal dimension and energy dissipation of cemented sand specimens under initial stress, which is so different from that under no initial stress. The experimental results in this study can be used to modify the fractal damage model for rock blasting considering the initial stress.